Development of 72 maize hybrids with high yield potential and competitive agronomic characteristics for the highlands, mid-altitudes and lowlands of Mexico - CGIAR Research Program on Maize (2020)
The selection of these 72 hybrids was based on the results of hybrids evaluation trials established in different localities of Mexico in the 2020 spring-summer season (such trials were established from four to seven localities).